GE_GERICHTE P/5540/2020 vom 22. März 2022 - GE Cour de justice (2022)
PLAIGNANT;LÉSÉ;CONSEIL D'ADMINISTRATION;MEMBRE;RADIATION(EFFACEMENT);REGISTRE DU COMMERCE;PROCÉDURE CIVILE;SUSPENSION DE LA PROCÉDURE | CPP.118; CPP.115; CPP.314